Cardiovascular autonomic neuropathy and bone metabolism in Type 1 diabetes. Issue 11 (20th August 2018) - Hansen, C. S.; Theilade, S.; Lajer, M.; Hansen, T. W.; Rossing, P.
Abstract: Aim: To investigate the association between cardiovascular autonomic neuropathy and bone metabolism in people with Type 1 diabetes. Methods: We assessed cardiovascular autonomic neuropathy in 329 people with Type 1 diabetes according to heart rate response to deep breathing, to standing and to the Valsalva manoeuvre, and 2‐min resting heart rate. More than one pathological non‐resting test was defined as cardiovascular autonomic neuropathy. Bone mineral density of the femoral neck (BMDfn) was assessed by dual energy X‐ray absorptiometry. Serum parathyroid hormone levels and other bone markers were measured. Results: The mean (sd ) age of the participants was 55.6 (9.4) years, 52% were men, and the mean (sd ) diabetes duration was 40 (8.9) years, HbA1c 62 (9) mmol/mol and estimated GFR 78 (26) ml/min/1.73m 2 . In all, 36% had cardiovascular autonomic neuropathy. Participants with cardiovascular autonomic neuropathy had 4.2% (95% CI –8.0 to –0.2; P =0.038) lower BMDfn and 33.6% (95% CI 14.3 to 53.8; P =0.0002) higher parathyroid hormone levels compared with participants without cardiovascular autonomic neuropathy in adjusted models. Higher resting heart rate remained associated with higher parathyroid hormone level and lower BMDfn after additional adjustment for eGFR ( P <0.0001 and P = 0.042, respectively). Conclusions: The presence of cardiovascular autonomic neuropathy was associated with reduced BMDfn and increased levels of parathyroid hormone. Kidney function may either confound or mediate these findings. Cardiovascular autonomic neuropathy could be associated with increased risk of osteoporosis in Type 1 diabetes. Whether cardiovascular autonomic neuropathy directly affects bone metabolism detrimentally or if this association is mediated via decreased kidney function should be investigated further. What's new?: People with diabetes have an increased risk of bone fractures, affected bone metabolism and autonomic dysfunction. Autonomic function has been associated with bone metabolism. An association between autonomic function and bone metabolism has not been fully investigated in Type 1 diabetes. Autonomic dysfunction assessed by measures of cardiovascular autonomic neuropathy was associated with decreased bone mineral density and increased levels of hormones regulating both bone resorption and bone formation. Kidney function was associated with most findings. Autonomic dysfunction could promote detrimental changes to bone metabolism in diabetes, increasing the risk of osteoporosis. Preventing autonomic dysfunction, could reduce the risk of bone fracture.